The Effect of Audit Quality on ESG Performance with Media Coverage as a Moderating Variable - Alfarizy, Muhammad Akmal; Sari, Vita Fitria (Universitas Negeri Padang, 2025)
Purpose – This study aims to examine the impact of audit quality on ESG performance with media coverage as a moderating variable in companies listed on the Indonesia Stock Exchange from 2020 to 2023 Design/methodology/approach –This study is a causal research utilizing a quantitative approach. The population for this research includes all companies in the listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The sampling method employed is purposive sampling. Findings – the result of this study find that audit quality, as proxied by the Big Four, does not have a significant impact on ESG performance while as proxied by the audit fees has positive effect on ESG performance. Media coverage as moderating variable does not moderate the relation between the big four and the audit fees on ESG performance. Originality/value – This study provides a novel contribution to the literature on audit quality and media coverage in relation to ESG performance First, it enriches the existing literature on audit quality and media coverage, which remains limited in emerging markets, particularly in Indonesia, by utilizing a measurement approach that differs from similar studies. Second, this research broadens the examination of media coverage which has been widely studied but has produced diverse results. Research limitations/implications – The results of this study indicate that the big four do not affect ESG performance, but audit costs do, and media coverage does not moderate the relationship between the three. The limited generalizability of the sample and research period in this study may provide an opportunity for further research. Future studies could explore a broader and specific range of industries, longer time periods, or different geographic regions to enhance the generalizability of the findings and provide deeper insights into the relationship between these factors and ESG performance. Keywords: ESG performance; audit quality; big four; audit fees; media coverageArticle Type: Research Paper